Sociocultural dimension of parents of premature infants discharged from a neonatal intensive care unit - Isis Vanessa Nazareth; Inês Maria Meneses dos Santos (Rev Rene, 2014)
This study aimed at identifying and analyzing the social and cultural dimensions of parents of premature infants discharged from neonatal intensive care units. It is a qualitative and descriptive study, based on ethno-nursing and in the Theory of Diversity and Universality Cultural Care with 12 participants. The setting was a university hospital in the city of Rio de Janeiro, RJ, Brazil. Data collection occurred between November, 2012 and April, 2013, through a social economic and cultural questionnaire and from the observation, participation and reflection. The analysis based on ethno-nursing and on the use of Atlas-ti software allowed to find the analytical category: the sociocultural structure of parents of premature infants discharged from a neonatal intensive care unit. Results should be used to promote a culturally relevant care and respecting the popular knowledge of parents while taking care of the children discharged from neonatal intensive care units.